Insulin resistance and β-cell function in Colombian mestizo and Embera-Chamí populations and their relation with adiposity degree (2017)
ABTRACT: Background and objective: Insulin resistance (IR) is a condition favored by metabolic and endocrine changes experienced by adipose tissue in the context of obesity. The prevalence and the presentation of both IR and obesity vary among the populations, and may be affected by ancestral genetic composition among other factors. The aim of this study was to compare the presence of IR and obesity in Amerindians of the Embera-Chamí ethnicity and Colombian mestizo population.